Assessment of Renal Functions among Saudi Arabian Pregnant Women in Jazan Region - Al-Elsukar, Akram Hamed Awad; Ahmed, Ahmed Mohammed (Arab Journal for Sciences and Research Publishing, 2015)
Marked renal hemodynamic changes are apparent by the end of the first trimester. Both the Glomerular filtration rate and effective renal plasma flow increase by 50% of pregnant women. Effective renal plasma flow probably increases to a greater extent, and thus, the filtration fraction is decreased during early and mid-pregnancy. Objectives: To assess the serum levels of renal functions among Saudi Arabian Pregnant women in Jazan region. Materials and Methods: a prospective, case- control hospital based study conducted in Jazan region from March 2014– June 2015.30 pregnant women selected in Jazan General Hospital and assessed for renal function tests. 30 healthy subjects selected as control group who were age, and socioeconomic matched to the pregnancy group. SPSS was used for data analysis using student’s ‟t” test and Pearson’s correlation for assessment of correlation between different variables. Results: There was a significant difference in the mean of the serum levels of urea and creatinine in test group (p<0.05) when compared to control group with a significant moderate positive correlation between serum levels of creatinine with the period of gestation. Conclusion: Serum levels of urea and creatinine significantly reduced in Saudi Arabian pregnant women. The progressive decrease in the levels of urea and creatinine through the 3 trimesters of pregnancy suggests an increase in Glomerular filtration rate, probably due to increased cardiac output, renal blood flow and changes in fluid distribution.